Pengaruh Jumlah Penduduk Dan Kemiskinan Terhadap Pertumbuhan Ekonomi Di Provinsi Jambi - Novelia Aliyah Pitri; Youdhi Prayogo; Laily Ifazah (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
To ensure that people in other developing countries can also enjoy the peace and prosperity brought about by Indonesia's economic development, Indonesia is actively seeking to spread its national economic growth model to these countries. The role of the Indonesian government in implementing development, especially in the economic sector, is very important for the country's success. In macroeconomics, a country's real income level is used as a proxy for its economic growth. Economic growth is the level at which a country's economy is able to increase the standard of living and the total income and standard of living of its citizens. When economists talk about the economy, they usually mean the rise in a country or region's standard of living each year. As a country's population increases, its consumption also increases, which in turn increases daily consumption levels, and demand on sources of income. Inequality and distribution of income is a result of economic growth that cannot be avoided if it does not include the utilization of existing sources of income.